2010
DOI: 10.1111/j.1600-0625.2010.01069.x
|View full text |Cite
|
Sign up to set email alerts
|

Novel ELISA systems for antibodies to desmoglein 1 and 3: correlation of disease activity with serum autoantibody levels in individual pemphigus patients

Abstract: Pemphigus vulgaris (PV) and pemphigus foliaceus (PF) are intraepidermal blistering skin diseases. PV is characterised by autoantibodies directed against desmoglein (Dsg) 3 and in patients with the mucocutaneous variant also against Dsg 1, whereas in PF, only Dsg 1 is targeted. Here, ectodomains of Dsg 3 and Dsg 1 were recombinantly expressed in a human cell line (HEK293) and applied as authentic solid phases in ELISA test systems. Autoantibodies against Dsg 3 and ⁄ or Dsg 1 could be detected in 71 (100%) of 71… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
87
2
11

Year Published

2012
2012
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 125 publications
(111 citation statements)
references
References 36 publications
6
87
2
11
Order By: Relevance
“…Some authors showed that serum anti-Dsg antibody levels reflect clinical activity during the disease course and indicate that monitoring of serum autoantibodies in PV may be helpful [10]; others observed that there was no correlation between variation in disease extent and the level of autoantibodies against Dsg3 and Dsg1 [34]. Further studies showed that anti-Dsg autoantibody levels were significantly reduced after treatment and remission of disease.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Some authors showed that serum anti-Dsg antibody levels reflect clinical activity during the disease course and indicate that monitoring of serum autoantibodies in PV may be helpful [10]; others observed that there was no correlation between variation in disease extent and the level of autoantibodies against Dsg3 and Dsg1 [34]. Further studies showed that anti-Dsg autoantibody levels were significantly reduced after treatment and remission of disease.…”
Section: Discussionmentioning
confidence: 99%
“…In detail, each field of the slide is a mosaic of 6 substrates: (1) frozen primate esophagus section; (2) EU90 recombinant cells transfected with Dsg1 protein ectodomain (aa 1–569) [10]; (3) EU90 recombinant cells transfected with Dsg3 protein ectodomain (aa 2–640) [10]; (4) EU90 recombinant cells transfected with full-length BP230 protein (aa 1–2649) [24]; (5) EU90 recombinant cells transfected with C-terminal globular domain of the BP230 protein (aa 1875–2649) [24]; (6) microdrops of NC16A-4X BP180 free antigen (tetramer of the immunogenic NC16A noncollagenosus domain of the BP180 protein, aa 490–562, expressed in Escherichia coli ) [18]. …”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…However, the study population was Indian, having a higher frequency of Dsg1 antibodies than European patients [13]. Other studies showed a correlation between Dsg ELISA findings and clinical status during follow-up [10,11,14,15], but still others did not find a correlation between Dsg1 ELISA results and cutaneous severity [16,17] or Dsg3 ELISA results and mucosal severity [18,19], including disease activity scoring with arbitrary and non-validated clinical activity scores [9,16,17]. In contrast, other studies did not find a correlation during follow-up [9,16,20].…”
Section: Discussionmentioning
confidence: 99%